A Light Weight 3x3 Switched Polarity URA Antenna and Receive System for Direction Finding - Depold, Andreas; Dorn, Christian; Erhardt, Stefan; Weigel, Robert; Lurz, Fabian (2022 IEEE Topical Conference on Wireless Sensors and Sensor Networks, WiSNeT 2022, 2022)
Minimizing the time it takes to locate and rescue victims from building collapses is critical for their survival chance. This scenario causes a challenging environment for radio frequency based localization. This paper introduces a direction finding system based on a 3x3 uniform rectangular array with integrated polarization switching for multipath mitigation intended for search and rescue applications. It is shown that utilizing two polarizations can be used to reduce or eliminate ambiguities caused by multipath propagation. Further approaches to optimize localization ability are discusse
CRIS-Team Scopus Importer:2022-04-15
Keywords: Antenna arrays; Direction-of-arrival estimation; phase detection; receivers